2002
DOI: 10.1074/jbc.m209341200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transport on Cis and Trans Sides of the Golgi Involves Two Distinct Types of Coatomer and ADP-ribosylation Factor-independent Transport Intermediates

Abstract: The cisternal maturation model proposes that secretory proteins transit the Golgi in cisternae that mature by the continuous retrograde transport of Golgi enzymes in vesicles. We have tested the hypothesis that de novo generation of transport intermediates containing medial, trans, and trans Golgi network (TGN) enzymes is reconstituted in vitro. Our analysis shows that the majority of transport is mediated by a steady state of transport intermediate production and consumption by Golgi cisternae, with only a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…This harsh treatment can result in the breakdown of perforated zones enriched in Golgi enzymes into small membrane fragments (Balch et al, 1984). Finally, Pullikuth and Weidman (2002) showed that the release of N-acetylglucosamine transferase and GalT into the supernatant, which apparently contained small membrane fragments, occurred in a COPIindependent manner during an incubation of isolated Golgi membranes with cytosol. Therefore, we propose that these fusion-competent, low-density membrane fractions containing the transferases are formed from perforated areas of cisternae.…”
Section: The Role Of Perforated Zones In Intra-golgi Transportmentioning
confidence: 99%
“…This harsh treatment can result in the breakdown of perforated zones enriched in Golgi enzymes into small membrane fragments (Balch et al, 1984). Finally, Pullikuth and Weidman (2002) showed that the release of N-acetylglucosamine transferase and GalT into the supernatant, which apparently contained small membrane fragments, occurred in a COPIindependent manner during an incubation of isolated Golgi membranes with cytosol. Therefore, we propose that these fusion-competent, low-density membrane fractions containing the transferases are formed from perforated areas of cisternae.…”
Section: The Role Of Perforated Zones In Intra-golgi Transportmentioning
confidence: 99%